PENILAIAN EFISIENSI BANK UMUM SWASTA NASIONAL DEVISA DAN BANK ASING DENGAN MENGGUNAKAN DATA ENVELOPMENT ANALYSIS (DEA) - Sulistiyo, Sulistiyo; Sumitro, Sumitro (MATEMATIKA, 2005)
Banking Industry the improvement of Indonesia cause increasing of competition level between bank, so the appraisal of bankâ€™s efficiency becomes more important, because the efficiency is the describes the performance of the company work. The method used to measure bank efficiency in this paper is Data Envelopment Analysis (DEA), a technic linear programming that calculating output ratio to input of each DMU. DMU is called efficient if the efficiency value is one, if the value is less than one it means DMU not efficient. DEA is also ready to give solution for other banks on sample which was not efficient to be more efficient. Bankâ€™s efficiency which is valuated in this paper are national commercial banks in Indonesia and foreign banks. The determination of input and output of bank based on bank behavior theory was using intermediation approach. The used optimization method in this paper to increase bank efficiency Â of inefficiency bank is optimization of input oriented method.